1991
DOI: 10.1089/lps.1991.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Segmental Resection of the Sigmoid Colon for Endometriosis

Abstract: We report a technique for laparoscopic segmental resection of the sigmoid colon. A 30.73-year-old nulligravida complained of pelvic pain, abdominal bloating, intestinal cramping, and painful bowel movements. Examination revealed significant nodularity of the posterior pelvis, so a preoperative bowel prep was given. At laparoscopy, a 5 cm diameter mid-sigmoid lesion was found, as well as a rectal nodule and pelvic endometriosis. The sigmoid lesion was separated from the mesocolon by bipolar electrocoagulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
11

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(81 citation statements)
references
References 2 publications
0
70
0
11
Order By: Relevance
“…Endometriosis miatt már több mint 25 éve végez-nek ilyen műtétet [15], a sebészek 3 éve alkalmazták elő-ször ezt a módszert [16]. Napjainkban már nemcsak a transrectalisan végzett specimeneltávolítás miatt került előtérbe, hanem az egyre szélesebb indikációval végzett transanalis endoszkópos mikrosebészet [17] és a kizáró-lag transrectalisan végzett rectumtumorműtétek -vagyis valódi NOTES-műtétek -miatt [18,19].…”
Section: Megbeszélésunclassified
“…Endometriosis miatt már több mint 25 éve végez-nek ilyen műtétet [15], a sebészek 3 éve alkalmazták elő-ször ezt a módszert [16]. Napjainkban már nemcsak a transrectalisan végzett specimeneltávolítás miatt került előtérbe, hanem az egyre szélesebb indikációval végzett transanalis endoszkópos mikrosebészet [17] és a kizáró-lag transrectalisan végzett rectumtumorműtétek -vagyis valódi NOTES-műtétek -miatt [18,19].…”
Section: Megbeszélésunclassified
“…Minimal access resections reduce the length of exposure incision while having a clear vision with magnification facilitating the resection (1). The first laparoscopic assisted left hemicolectomy performed in 1991 reported to have reduced morbidity (2). The problems associated with the new learning curve became less over time, whilst providing clear benefits (1,(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Large published studies, randomized trials and meta-analyses suggest an average length of hospital stay of about ten days (Bokey et al, 1995;Abraham et al, 2004Abraham et al, & 2007. In an attempt to mimic the success of laparoscopic gall bladder surgery, laparoscopic colorectal resection was introduced in 1991 as a proposed less invasive alternative to the open technique (Jacobs, 1991;Redwine, 1991). Under conventional circumstances, in the first published series of 20 laparoscopic sigmoid colectomies, the authors reported that a five-day hospital stay was achieved in 70% of patients.…”
Section: Introductionmentioning
confidence: 99%